2021
DOI: 10.1101/2021.01.07.425721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiomics Integration Elucidates Metabolic Modulators of Drug Resistance in Lymphoma

Abstract: BackgroundDiffuse large B-cell lymphoma (DLBCL) is the most common non-Hodgkin lymphoma (NHL). B-cell NHLs rely on Bruton’s tyrosine kinase (BTK) mediated B-cell receptor signaling for survival and disease progression. However, they are often resistant to BTK inhibitors or soon acquire resistance after drug exposure resulting in the drug tolerant form. The drug tolerant clones proliferate faster, have increased metabolic activity, and shift to oxidative phosphorylation; however, how this metabolic programming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Metabolic reprogramming is well studied in B-cell lymphoma [5][6][7] including diffuse large B-cell lymphoma (DLBCL) [8][9][10][11]. A recent analysis of fresh tumor specimens by the multi-omics approach has allowed refining DLBCL patient classifications into distinct subtypes and predicting therapies [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic reprogramming is well studied in B-cell lymphoma [5][6][7] including diffuse large B-cell lymphoma (DLBCL) [8][9][10][11]. A recent analysis of fresh tumor specimens by the multi-omics approach has allowed refining DLBCL patient classifications into distinct subtypes and predicting therapies [12].…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, in vitro studies to understand the basic metabolic reprogramming of DLBCL cell lines are conducted in a two-dimensional (2D) culture [9,11,[18][19][20]. On the other hand, it has been observed that cancer cells proliferate at an unnatural pace in 2D and sometimes yield confounding results from experimental investigations [21][22][23].…”
Section: Introductionmentioning
confidence: 99%